2015
DOI: 10.1080/10447318.2015.1094914
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Haptic Feedback and Visual Distraction on Pointing Task Performance

Abstract: Previous research has not fully examined the effect of additional sensory feedback, particularly delivered through the haptic modality, in pointing task performance with visual distractions. This study examined the effect of haptic feedback and visual distraction on pointing task performance in a 3D virtual environment. Results indicate a strong positive effect of haptic feedback on performance in terms of task time and root-mean square error of motion. Level of similarity between distractor objects and the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Similar methods were applied in a more recent study by Lin and Woldegiorgis to report egocentric distance estimation in a depth plane of a virtual environment. Furthermore, reaching with vision was reported to be better and smoother and using avatars and haptic feedback, Camporesi and Kallmann and Corbett et al, respectively, claimed that the quality of motions has been improved. To accommodate the considered distance, the hand reaching was extended by holding pointing sticks, at which reflective markers were attached at their tips.…”
Section: Methodsmentioning
confidence: 99%
“…Similar methods were applied in a more recent study by Lin and Woldegiorgis to report egocentric distance estimation in a depth plane of a virtual environment. Furthermore, reaching with vision was reported to be better and smoother and using avatars and haptic feedback, Camporesi and Kallmann and Corbett et al, respectively, claimed that the quality of motions has been improved. To accommodate the considered distance, the hand reaching was extended by holding pointing sticks, at which reflective markers were attached at their tips.…”
Section: Methodsmentioning
confidence: 99%
“…Haptic feedback is a method of providing feedback that recreates the sense of touch through the use of motors and vibrations; this allows people to experience real sensations which can significantly affect emotional well-being and has been shown to successfully improve mental well-being [178], [179]. Good vibes [180] used a haptic sleeve to provide varying feedback dependent on heart rate readings.…”
Section: Real-time Tangible Feedback Interfacesmentioning
confidence: 99%
“…According to Anderson (1979), nonverbal haptic feedback, aimed more toward regulation, correction, and student encouragement, includes technical, emotional, motivational, and relational functions (Bonneton-Tabarie`s & Lambert-Libert, 2006). Recently, Corbett, Nam, and Yamaguchi (2016) demonstrated that haptic feedback benefited a pointing task performed under visual distractions.…”
Section: Introductionmentioning
confidence: 99%